2008
DOI: 10.1002/ceat.200800100
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Energy Consumption and Greenhouse Gas Emissions in a Plant for the Separation of Amines

Abstract: The chemical industry comprises of the companies that produce industrial chemicals. It is central to the modern world economy, converting raw materials into more than 70 000 different products. However, environmental regulations and the risk of climate change are putting pressure on the chemical industry to minimize greenhouse gas emissions. In this work, we use the concept of process intensification (using thermally coupled distillation) to reduce energy consumption and CO 2 emissions in a plant for the separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…35 In this case we cover a sufficiently complete range of frequencies. Similar studies have been reported by Jantes-Jaramillo et al, 36 G omez-Castro et al, 37 Ibarra-S anchez and Segovia-Hern andez 38…”
Section: Singular Value Decomposition (Svd)supporting
confidence: 86%
See 1 more Smart Citation
“…35 In this case we cover a sufficiently complete range of frequencies. Similar studies have been reported by Jantes-Jaramillo et al, 36 G omez-Castro et al, 37 Ibarra-S anchez and Segovia-Hern andez 38…”
Section: Singular Value Decomposition (Svd)supporting
confidence: 86%
“…In this case we cover a sufficiently complete range of frequencies. Similar studies have been reported by Jantes-Jaramillo et al, Gómez-Castro et al, Ibarra-Sánchez and Segovia-Hernández among others, for control analysis in studies of thermally coupled distillation systems.…”
Section: Singular Value Decomposition (Svd)supporting
confidence: 85%
“…In this case a sufficiently complete range of frequencies was covered. Similar studies have been reported by Jantes-Jaramillo et al [23], Gómez-Castro et al [18,24], and Ibarra-Sánchez and Segovia-Hernández [25] among others, for the control analysis of complex distillation systems. Other techniques available for the dynamic analysis of distillation systems are the relative gain array (RGA) analysis and the Niederlinski Index (NI) analysis, which allows to determinate the best pairing alternatives between control loops [26].…”
Section: Singular Value Decomposition Technique (Svd)supporting
confidence: 85%
“…Large amounts of CO 2 is emitted into the atmosphere and has a rather long atmospheric lifetime [1]. In order to achieve a reduction in the CO 2 release, practical methods such as energy saving, improvement of conversion efficiency, and development of alternative energy sources must be implemented [2].…”
Section: Introductionmentioning
confidence: 99%